Genealogi Paradigma Fiqh Progresif di Pesantren (Studi Atas Cikal-Bakal Berdirinya Ma'had Aly Al-Qism al-Fiqh di Pondok Pesantren Salafiyah Syafi’iyyah Sukorejo Situbondo): Genealogy of the Progressive Fiqh Paradigm in Islamic Boarding Schools (A Study on the Origins of Ma'had Aly Al-Qism al-Fiqh at Salafiyah Syafi’iyyah Sukorejo Islamic Boarding School, Situbondo) - Pujiono Abd. Hamid (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2014)
Due to the strong tendency toward orthodoxy and orthopraxy, the fiqh tradition in Islamic boarding schools generally moves toward a conservative character and paradigm. Ma'had Aly al-Qism al-Fiqh exhibits a different tendency, showcasing a progressive face and paradigm in the study of Islamic law. This research employs an